Sonographic Evaluation of Pancreatic Morphology in Patients with Diabetes Mellitus - Ghimire, Prasanna; Ghimire, Pragya Gautam; Paudel, Nabin; Jha, Amit; Ranabhat, Roshani; Jha, Sushmita; Singh, Avinash Kumar; Subedi, Shreya (Journal of Nepalgunj Medical College, 2025)
Introduction: Diabetes mellitus is a chronic metabolic disorder linked to pancreatic structural changes detectable by imaging. This study evaluates pancreatic size and echogenicity in Type 1 and Type 2 diabetes mellitus compared to healthy controls, emphasizing sonography’s utility in resource-limited settings where advanced imaging is scarce. Aims: To assess pancreatic morphological changes via ultrasound in Type 1 and Type 2 diabetes patients, correlating findings with clinical parameters such as disease duration, HbA1c, and body mass index. Methods: A prospective cross-sectional study included 300 subjects: 100 Type 1, 100 Type 2 diabetes mellitus and 100 age- and sex-matched healthy controls. Standardized fasting transabdominal ultrasound measured anteroposterior diameters of the pancreatic head, body, and tail were taken. Echogenicity was graded (0–3) relative to liver echogenicity. Clinical data disease duration, HbA1c, and body mass index were collected. Statistical analyses compared groups and assessed correlations. Results: Type 1 diabetes mellitus patients exhibited marked pancreatic atrophy across all segments, with the most severe reduction in the tail. Type 2 diabetes patients showed mild reduction in pancreatic head diameter but relatively preserved body and tail dimensions. Pancreatic size inversely correlated with disease duration in Type 1 (r=−0.45, p<0.001) and Type 2 Diabetes (r=−0.28, p<0.001). Increased echogenicity was observed in 68% of Type 1 and 72% of Type 2 patients, versus 12% of controls. In Type 2 patients, echogenicity positively correlated with body mass index (r=0.34, p<0.001). Conclusion: Sonography is a valuable, non-invasive, and cost-effective tool for assessing pancreatic changes in diabetes. Type 1 diabetes mellitus is associated with marked pancreatic atrophy correlating with disease duration, while Type 2 diabetes mellitus demonstrates primarily increased echogenicity related to fatty infiltration and body mass index, with only mild size reduction. These findings highlight sonography’s potential as a primary diagnostic and monitoring tool in resource-limited settings.